Methodological basis monitoring the effectiveness of implementation of regional programs «Environment-2015» in Poltava region - Голік, Ю. С.; Ілляш, О. Е. (Man and Environment. Issues of Neoecology)
The analysis of the methodological principles of the implementation of national environmental policy at the regional level, the experience of the formation of an environmental planning and management in the Poltava region. Dedicated main stages, which should be in strategic environmental planning. Methodological background of the monitoring and evaluation of the implementation of regional environmental programs as an example of the «Environment-2015» in Poltava region, which take into account European guidelines and personal experience of the region in the field of environmental protection.